PEMENUHAN HAK-HAK ANAK SEBAGAI KORBAN KEKERASAN SEKSUAL OLEH PENGEMUDI OJEK ONLINE (STUDI PUTUSAN NOMOR 455/PID.SUS/2024/PN. SBY) - Prastiawan, Andi; Apriyani, Maria Novita (Universitas Labuhanbatu, 2025)
This study addresses the issues in Decision Number 455/Pid.Sus/2024/PN Sby concerning the judge's considerations in fulfilling the rights of a child victim of sexual crimes committed by an online motorcycle taxi driver. This paper employs normative legal research methods. The findings indicate that the panel of judges based their fulfillment of the victim’s rights on both juridical and non-juridical considerations. Juridical aspects include the indictment by the public prosecutor, the defendant’s testimony, witness statements, submitted evidence, and provisions within criminal law. Non-juridical aspects encompass the defendant’s background, the impact of the offense, the defendant’s personal circumstances, and the surrounding socio-economic conditions. The judge’s considerations in rendering the verdict are deemed to have not fully fulfilled the sense of justice for the victim.Keywords: Child; Fulfillment of Rights; Judicial Consideration; Sexual Violence Crime